2019
DOI: 10.14254/2071-8330.2019/12-2/7
|View full text |Cite
|
Sign up to set email alerts
|

Gold and capital market in Indonesia: A preview on strategy of hedging and diversification

Abstract: This study examines the establishment of a portfolio among sharia stocks represented by the Jakarta Islamic Index (JII) with gold (gold futures contracts). Gold price used in this research was the gold price in the international market which was in USD denomination and also converted into Rupiah (IDR), by considering commodity futures instruments in Indonesia using fixed rate or floating rate option. The data analysis technique used in this research was the dynamic portfolio formulation by using Dynamic Condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
4
3
0
2
Order By: Relevance
“…Gold and Bitcoin can be considered as safe havens during the global pandemic when investing in the NYSE energy stocks. This result is consistent with that of Gaspareniene et al ( 2018 ) and Robiyanto et al ( 2019 ). However, it is inconsistent with that of Conlon and McGee ( 2020 ) and Corbet et al ( 2020 ).…”
Section: Data and Resultssupporting
confidence: 94%
“…Gold and Bitcoin can be considered as safe havens during the global pandemic when investing in the NYSE energy stocks. This result is consistent with that of Gaspareniene et al ( 2018 ) and Robiyanto et al ( 2019 ). However, it is inconsistent with that of Conlon and McGee ( 2020 ) and Corbet et al ( 2020 ).…”
Section: Data and Resultssupporting
confidence: 94%
“…The average yield of a portfolio formed from stocks and gold is greater than the average recorded from using only the stock portfolio. The findings from the Sharpe and Sortino Ratios are in line with the results of Robiyanto (2018), El Hedi Arouri et al, (2015, Hoang et al, (2015), and Robiyanto, Hadiyatno, et al, (2019) which showed the portfolio formed from stocks and gold to better than those obtained from stocks alone.…”
Section: T-test Resultssupporting
confidence: 84%
“…Moreover, portfolios with gold are believed to have the ability to produce significantly better performance (El Hedi Arouri et al, 2015) and this is associated with the negative correlation of its nature to other assets which makes it a good factor in portfolio diversification due to the usual increase in its price when the price of other assets reduce (Hoang, Lean, and Wong, 2015). Robiyanto, Hadiyatno, Sudjinan, and Ernayani (2019) also found the performance of a stock portfolio to improve due to the inclusion of gold. These arguments, therefore, led to the formulation of the following hypothesis : the performance of the dynamic portfolio formed from combining LQ-45 stocks and gold is better than those formed with LQ-45 stocks alone.…”
Section: Gold and Stocks Portfolio During Covid-19mentioning
confidence: 99%
“…This result indicates that bond markets sustain the traditional role as a hedge for the equities, at least on average. While this result is consistent with Ciner et al (2013), however, this result is also in line with Robiyanto et al (2019aRobiyanto et al ( , 2019b who suggested that government bonds are not simply diversifier instruments, but also have roles as a safe haven and hedge in the Indonesian capital market. This condition may exist since Indonesian and Malaysian government bonds are in demand by foreign investors (Gusdinar and Koesrindartoto 2013).…”
Section: Discussionsupporting
confidence: 86%
“…This research utilized the Dynamic Conditional Correlation (DCC) process proposed by Engle (2002). The method was used for the construction of the portfolio that consists of equities, gold, and oil in previous studies such as Arouri et al (2014); Maghyereh et al (2017); Robiyanto et al (2019aRobiyanto et al ( , 2019b; Robiyanto et al (2017). This model can capture time-varying and dynamic correlation using the return series without complex calculations.…”
Section: Dynamic Conditional Correlation-generalized Autoregressive Cmentioning
confidence: 99%